2017
DOI: 10.18632/oncotarget.15499
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of miR-520c leads to induced S100A4 expression and its mediated colorectal cancer progression

Abstract: The S100 calcium-binding protein A4 (S100A4) induces epithelial mesenchymal transition, migration, invasion, angiogenesis and metastasis. Its induced expression in several cancer types correlates with poor prognosis. Apart from the functional and transcriptional regulatory aspects of S100A4, its post-transcriptional regulation is not yet clearly elucidated. In this study, we show that microRNAs (miR) miR-505-5p and miR-520c-3p target the 3′-UTR of S100A4 and inhibits its expression and its mediated migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…The epigenetic regulation of genes is widely involved in cancer development . Previous studies have reported that canonical DNA methylation induced a low expression of miRNAs in various kinds of cancers . Our results indicate that such a mechanism also exists in the downregulation of miR‐520c‐3p in LUAD.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The epigenetic regulation of genes is widely involved in cancer development . Previous studies have reported that canonical DNA methylation induced a low expression of miRNAs in various kinds of cancers . Our results indicate that such a mechanism also exists in the downregulation of miR‐520c‐3p in LUAD.…”
Section: Discussionsupporting
confidence: 60%
“…A few previous studies reported that microRNA‐520c‐3p (miR‐520c‐3p) plays important roles in several kinds of malignant diseases, including lymphoma , breast cancer , fibrosarcoma , hepatocellular carcinoma (HCC) , colorectal cancer (CRC) , glioma , prostate cancer , and gastric cancer . Of these studies, some indicated that miR‐520c‐3p facilitates tumor growth .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent study has demonstrated that miR-520c-3p negatively regulates epithelial-mesenchymal transition (EMT) by targeting IL-8 to suppress the invasion and migration of breast cancer [16]. In addition, miR-520c-3p could target the 3'-UTR of S100A4 and inhibits its expression and its mediated migration and invasion of colorectal cancer [17].…”
Section: Introductionmentioning
confidence: 99%